Effects of Different Pretreatments to Fresh Fruit on Chemical and Thermal Characteristics of Crude Palm Oil. Issue 12 (14th November 2017) - Tang, Minmin; Xia, Qiuyu; Holland, Brendan J.; Wang, Hui; Zhang, Yufeng; Li, Rui; Cao, Hongxing
Abstract: This study selected 5 methods, including boiling, hot air drying, high‐pressurized steam, freezing, and microwave radiation to pretreat fresh oil palm fruit before solvent extraction of the oil. Using fresh fruit as a control, the pretreatment methods were compared for the effects on the activity of the 2 main enzymes in the fruit and some physicochemical properties of the crude palm oil. The results indicated, although all the 5 pretreatments could inactivate lipase and peroxidase in the treated flesh significantly ( P < 0.05), the high‐pressurized steam was the most effective. There were also differences in the unsaturated fatty acid contents of the 6 oils. The crude oil from frozen fruit contained significantly more vitamin E (37829.33 ppm) than previously reported. Microwave radiation was shown to significantly decrease the free fatty acid content and the peroxide value, while increasing the oxidative stability index. Thermal behaviors of the oils were significantly different to each other with the exception a few parameters ( P < 0.05).